SAT0467 Cerebral venous thrombosis occurrence in systemic lupus erythematosus without anti-phospholipid antibody syndrome: a monocentric serie of 10 cases. (12th June 2018) - Lepine, Z.; Mathian, A.; De Chambrun, M. Pineton; Cohen, F.; Haroche, J.; Hie, M.; Pha, M.; Amoura, Z.
Abstract : Background: Cerebral venous thrombosis (CVT), which includes cerebral vein and dural sinus thrombosis, is a rare disorder that can lead to significant morbidity and mortality. Its occurrence in SLE in the absence of APS has been rarely reported. In this study we aimed to describe a cohort of SLE patients suffering from CVT without APS. Methods: We collected retrospectively clinical and biological data of patients with confirmed CVT in the Pitié-Salpêtrière cohort of SLE (n=1352 patients). Patients fulfilled ACR SLE criteria. The diagnosis of CVT was confirmed by brain imaging studies. Exclusion criteria were patient with a lupus anticoagulant or IgG/IgM anticardiolipin antibodies or anti-β2 glycoprotein-1 abs. We searched on PUBMED database for case report of this association published in English until 31 August 2017. Lupus flares were defined according the SELENA Flare instrument. Results: We included 10 patients (8 women and 2 men). The median (range) age at diagnosis of CVT was 28 years. 9–53 The CVT occurred with a median delay of 4 years (0–11) after the diagnosis of SLE. At the time of the CVT diagnosis: no patients had a past medical history of thrombotic event or miscarriage or foetal loss; 7 patients had a lupus flare (5 lupus nephritis [1 class I, 1 class V, 2 class IV and 1 class III+V], 4 immune thrombocytopenia, 2 autoimmune hemolytic anaemia, 3 cutaneous lupus, 1 serositis and 1 arthritis); 7 patients were treated with corticosteroids, 4 with hydroxychloroquine and 4 with immunosuppressive drugs. Other potential precipiting factors of CVT were: 2 nephrotic syndromes, 2 anaemia and 1 hyperhomocysteinemia. CVT was symptomatic for 9 patients: 8 headaches, 3 epilepsia and 1 sensitivo-motor deficit. The diagnosis of CVT was confirmed by magnetic resonance imaging (MRI) for 9 patients and cerebral angiography for 1 patient. The median delay between the onset of clinical symptoms and the diagnosis of thrombosis was 10 days. 3–37 Nine patients presented a single localisation of CVT (superior longitudinal or lateral or cavernous sinus, or cortical cerebral vein). Only 1 patient had thrombosis of both lateral and sigmoid sinus. Cerebral infarction or haemorrhage was seen for 2 patients. Corticosteroids and immunosuppressant treatment were increased or introduced because of a concomitant lupus flare for 2 patients. All patients were treated with heparin followed by vitamin K antagonists for 7 patients or apixaban for 2 patients. One patient received long-term heparin. After a median survey of 19.5 (1–120) months: anti-coagulant drugs were stopped for 6 patients; recanalisations were complete in 7 of the 7 patients assessed on brain MRI; no patient had a residual neurological damage; only 1 patient had a new vascular event in the form of a brain haemorrhage. In addition to these 10 cases we found 17 cases from a literature review. Conclusions: CVT is a rare event in SLE in absence of APS. In our cohort SLE was often active at the time of the CVT occurrence. Most of the CVT were limited in extension and severity. The outcome on anticoagulant treatment was favourable without residual neurological damage. The occurrence of CVT in SLE is not an indication by itself to increase or to introduce corticosteroids or immunosuppressive drug. Disclosure of Interest: None declared